PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KOPERASI TIRTA LESTARI - Lusiana, Herlina; Khuzaini, Khuzaini; Mursanto, Mursanto (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
This study aims to analyze the impact of leadership style and organizational culture on employee performance with job satisfaction as an intervening variable at Koperasi Tirta Lestari. The research employs a quantitative approach with a survey method to collect data from Koperasi Tirta Lestari employees. Data analysis is conducted using Partial Least Square (PLS) and processed with Smart PLS 3.0 software. The results indicate that leadership style has a significant positive effect on both employee performance and job satisfaction at Koperasi Tirta Lestari. Organizational culture does not have a significant effect on employee performance, but it does have a significant positive impact on job satisfaction at Koperasi Tirta Lestari. Job satisfaction does not have a significant effect on employee performance at Koperasi Tirta Lestari. Furthermore, job satisfaction does not mediate the relationship between leadership style and employee performance, nor does it mediate the relationship between organizational culture and employee performance at Koperasi Tirta Lestari